PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL HASIL PRODUK UMKM ERA DIGITALISASI (Jurnal Magister Hukum Perspektif, 2022)
This research examines the Legal Protection of Intellectual Property Rights from the Results of Micro, Small and Medium Enterprises Products in facing the Digitalization Era, in the modern era there are many new entrepreneurs emerging in the business world, the existence of Businesses, Micro, Small, and Medium Enterprises is quite widely found. The purpose of this study is to determine the importance of protection from the results of Micro, Small and Medium Enterprises products in facing the digitalization era. The research method used is the normative juridical method, namely legal research carried out using library materials or secondary data which includes primary legal materials from laws and regulations and secondary legal materials from articles and books. The result of this study is that efforts to protect the legal results of Micro, Small and Medium Enterprises products in facing the digitalization era for business actors can be carried out through the role of the government by responding to technological advances by means of online digitalization. This step can make it easier for Business, Micro, Small, and Medium Enterprises to gain insight into the importance of protection. The innovation of Micro, Small and Medium Enterprises in creating a product continues to emerge, so that their intellectual property rights must be protected, this is the strength of the competitiveness of Micro, Small and Medium Enterprises in business. Keywords: Digitalization, Intellectual Property Rights, Protection, Micro, Small and Medium Enterprises.